Adapting development: improving services to the poor - Wild, Leni; Booth, David; Cummings, Clare; Foresti, Marta; Wales, Joseph (ODI, 2015)
On current trends, it will take decades or longer to bring basic servi ces to the world’s most disadvantaged people. Meeting this challenge m eans recognising the political conditions that enable or obstruct deve lopment progress - a radical departure from the approach of the Millen nium Development Goals.
Keywords: Practice